The existence of equilibrium in a financial market with transaction costs - Xing Jin; Frank Milne (Queen's University, Department of Economics, 1999)
This paper proves the existence of a general equilibrium in a financial model with transaction costs. A general equilibrium is shown to exist in a model with convex trading technology, in which the agents include consumers, production firms, brokers or dealers. When the trading technology is non-convex, an individual approximate equilibrium, introduced by Heller and Starr (1976) is proved in the above model. And, moreover, under a further assumption of finite p-convexity on the commodity excess demand correspondence, a general equilibrium for a non-convex exchange economy is obtained for an economy with consumers, brokers or dealers.
Keywords: 330; arbitrage; general equilibrium; transaction cost; individual approximate equilibrium; finite p-convexity